Governance of the Hajj Financial Management Agency (BPKH) Based on Sharia Governance Principles - Changir, Siti Angelina Pratiwi; Febriani, Dewi (Halal Tourism and Pilgrimage, 2024)
This study aims to analyze the implementation of governance of the Hajj Financial Management Agency (BPKH) according to the Sharia Governance Guidelines from KNKG, including understanding sharia principles in managing hajj funds, identifying obstacles in its implementation, and how to overcome these obstacles. The study uses a qualitative descriptive method that evaluates BPKH governance based on the principles of sharia governance within the Indonesian legal framework. The research approach includes socio-economic analysis with primary data from related Laws and Government Regulations, as well as secondary data from sources such as BPKH annual reports, journals, Islamic books, and credible articles. Researchers found that overall, the implementation of BPKH governance based on sharia entity governance in Indonesia has been very good, with an implementation rate of 89%. Although principles 1 and 2 still need improvement to achieve perfection, BPKH has shown strong commitment and significant achievements in various aspects of governance.